Air flow effect on the temperature of a building integrated PV-panel - Aresti, Lazaros; Agathokleous, Rafaela; Christodoulides, Paul; Kalogirou, Soteris A. (My University, 2013)
This study examines the effect of air flow between the building integrated PV-panel and the wall of the building. To formulate the heat exchange process for a fluid flowing between the PV panel and the building wall, time-dependent, partial heat transfer differential equations (PDEs) are used and solved with the COMSOL simulations program. It is shown that in summer, the maximum temperature of a PV panel is observed on an east facing surface. The maximum temperature for a south facing panel is lower by about 27°C and that for a west facing surface by about 19°C. The air velocity in the air-gap between the PV-panel and the building wall lowers the mean temperature of the panel by about 35°C allowing for a significant increase in its efficiency. Finally the air-gap width is varied, keeping a steady velocity, and its effect is studied with respect to the temperature of the PV-panel.
Keywords: Integrated PV-panel; Air flow simulation; Air-gap